If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(x + 3) + 4x + 5 = 6x + 12 Reorder the terms: -9(3 + x) + 4x + 5 = 6x + 12 (3 * -9 + x * -9) + 4x + 5 = 6x + 12 (-27 + -9x) + 4x + 5 = 6x + 12 Reorder the terms: -27 + 5 + -9x + 4x = 6x + 12 Combine like terms: -27 + 5 = -22 -22 + -9x + 4x = 6x + 12 Combine like terms: -9x + 4x = -5x -22 + -5x = 6x + 12 Reorder the terms: -22 + -5x = 12 + 6x Solving -22 + -5x = 12 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -22 + -5x + -6x = 12 + 6x + -6x Combine like terms: -5x + -6x = -11x -22 + -11x = 12 + 6x + -6x Combine like terms: 6x + -6x = 0 -22 + -11x = 12 + 0 -22 + -11x = 12 Add '22' to each side of the equation. -22 + 22 + -11x = 12 + 22 Combine like terms: -22 + 22 = 0 0 + -11x = 12 + 22 -11x = 12 + 22 Combine like terms: 12 + 22 = 34 -11x = 34 Divide each side by '-11'. x = -3.090909091 Simplifying x = -3.090909091
| 8(31.25+-0.5y)+4y=250 | | 3(30+s)=4(s+1a) | | 2w+6=30 | | 2m+1=6m+2 | | 8(31.25+-0.5)+4y=250 | | x^4+6x^2+2x=0 | | 21m+36=3m | | 14x-21=49 | | (1/6x-5)-(6/5-6x) | | 8(x-9)=12 | | -3.4=.4j | | 49=25/1y | | 7c-7b=x | | 3(x+7)-4(x+3)=10 | | 12+50=949.88 | | 6y+(-4)= | | -2x=5x-9x+16-10 | | 7=.75*20+4 | | -3/4*8 | | 3+66x=33x+22 | | -x/4=-22 | | 4(7x+1)=312 | | .6h=1.8 | | 2(3y-6)= | | 8x+3y=101 | | -4(8+5x)=-32 | | 14=4a+2 | | 5x+11=7-2x | | -94=-2(5m+7) | | -2(7x-5)+3=-14x+13 | | p/7=6.8.k/4=2 | | 3x+11=12+8x |